Endo-perio lesions prevalence in non-molar and molar teeth: a pilot study - Flávia Cristina Castilho CUCOLO; Mariana Costa BONVALENTE; Eliane Marçon BARROSO; Benedicto Egbert Corrêa de TOLEDO; Gabriela Alessandra da Cruz Galhardo CAMARGO; Alessandra Areas e SOUZA; Elizangela Cruvinel ZUZA (Universidade Estadual Paulista, 2021)
Abstract Introduction Pulp and periodontal tissues may communicate and, in pathological situations, combined endodontic-periodontal lesions may be established. Objective The aim of this study was to evaluate the prevalence of endo-perio lesions in non-molar and molar teeth referred for endodontic treatment. Material and method The sample consisted of 104 teeth evaluated in 79 consecutive patients in a cross-sectional design. Visible plaque, probing depth, and bleeding on probing were evaluated. Endodontic evaluation included the presence or absence of caries, fistulas, pain, and pulp sensitivity. The presence/absence of periapical lesion, bone loss in the furcation region, and proximal area were evaluated. Result The results showed that pain was the main reason for seeking dental care in 63.3% of patients. The molar teeth demonstrated higher presence of probing depth (PD) ≥ 7 mm (38.3%) and higher PD mean (6.17 mm) than non-molar teeth (P<0.05). It was verified that 65.4% of the teeth were diagnosed with a primary endodontic lesion and that the periodontal component was present in 34.6% of the teeth, either in a primary (10.6%), secondary (11.5%), or combined form (12.5%). True combined endodontic-periodontal lesion occurred significantly in molar teeth compared to non-molar teeth (p<0.05). Conclusion The primary endodontic lesion was found in a greater proportion in teeth referred for endodontic treatment; however, approximately 1/3 of the sample had periodontal involvement, which demonstrates the importance of the periodontal examination together with the general clinical examination.